Temporal patterns of visitation of birds and mammals at mineral licks in the Peruvian Amazon. Issue 24 (11th November 2020) - Griffiths, Brian M.; Bowler, Mark; Gilmore, Michael P.; Luther, David
Abstract: Mineral licks are key ecological resources for many species of birds and mammals in Amazonia, providing essential dietary nutrients and clays, yet little is known about which species visit and their behaviors at the mineral licks. Studying visitation and behavior at mineral licks can provide insight into the lives of otherwise secretive and elusive species. We assessed which species visited mineral licks, when they visited, and whether visits and the probability of recording groups at mineral licks were seasonal or related to the lunar cycle. We camera trapped at 52 mineral licks in the northeastern Peruvian Amazon and detected 20 mammal and 13 bird species over 6, 255 camera nights. Generalized linear models assessed visitation patterns and records of groups in association with seasonality and the lunar cycle. We report nocturnal curassows ( Nothocrax urumutum ) visiting mineral licks for the first time. We found seasonal trends in visitation for the black agouti ( Dasyprocta fuliginosa ), red howler monkey ( Alouatta seniculus ), blue‐throated piping guan ( Pipile cumanensis ), red brocket deer ( Mazama americana ), collared peccary ( Pecari tajacu ), and tapir ( Tapirus terrestris ). Lunar trends in visitation occurred for the paca ( Cuniculus paca ), Brazilian porcupine ( Coendou prehensilis ), and red brocket deer. The probability of recording groups (>1 individual) at mineral licks was seasonal and related to lunar brightness for tapir. Overall, our results provide important context for how elusive species of birds and mammals interact with these key ecological resources on a landscape scale. The ecological importance of mineral licks for these species can provide context to seasonal changes in species occupancy and movement. Abstract : Many species of animals in the Amazon visit mineral licks, consuming soil to supplement their diet. Using camera trap data, we show that visits to mineral licks are seasonal for many species. These trends in visitation are likely due to species‐specific factors such as reproduction, predator avoidance, seasonal diet shifts, and resource use.